Psychosocial rehabilitation: income generating workshop in the mental health context - de Oliveira Lussi, Isabela Aparecida; Simões Matsukura, Thelma; Hahn, Michelle Selma (O Mundo da Saúde, 2010)
One of the great challenges placed by the intervention in mental health is the difficulty of users’ access to a productive life. Despite all progresses, paradigm changes and implemented practices and psychosocial rehabilitation, the inclusion in the work world still is an important barrier to be transposed for reaching better levels of quality of life and more concrete conditions of social inclusion. The present study aimed at identifying the main demands, challenges, difficulties and chances considered by professionals who carry through income generation workshops and/or cooperatives. From the localization and mapping of existing workshops in State São Paulo, five experiences were chosen. Data collection occurred by means of visits and interviews carried through with the professionals responsible for the workshops. The results had allowed the elaboration of a diagnosis characterizing the experiences developed within a contextualized analysis. It is argued that although experiences are making possible insertion realities, it is necessary to have a critical attitude about how much must still be developed for promoting autonomy and the development of citizenship of involved subjects.